Face to Face Mode vs. Online Mode: A Discrepancy in Analogy-Based Learning During COVID-19 Pandemic (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Reasoning skill is crucial for students to translate the learning material provided by the teacher in online mode during the COVID-19 pandemic. Many teachers choose analogy-based learning to explain a concept by bringing the concept to facts that are close to students’ daily lives. Analogy-based learning that was carried out face-to-face before the pandemic improved students’ reasoning skills, and now its implementation is tested in online mode. The study aims to analyze differences in reasoning skills in each indicator area and their factors. A significant difference was obtained by involving 72 students and doing a t-test for two data groups in the two sample groups. Students’ skills to identify problems and apply concepts have increased even though it is not as good as the increase in both aspects on face-to-face mode. The other two aspects (exploring the facts and concluding) are very unsatisfactory. There is a striking discrepancy between analogy-based learning during and before the pandemic with an unchanged syntax but different situations. The reduction in each reasoning indicator ranged from 10% to 25%. Signal constraints, a less supportive learning environment, and delayed communication between teachers and students are the main factors. This study provides an overview of discrepancies that can be addressed more wisely by strengthening the function of the media to optimize teacher and students communication and learning innovations that help students’ learning difficulties during the pandemic.